Diatomáceas do paleógeno do platô de São Paulo (dsdp leg 39, site 356) - Paier, Carina (Universidade do Vale do Rio dos Sinos, 2011)
Diatoms are excellent biostratigraphic markers to Meso-Cenozoic Eras and are a very useful elements to paleoecologic and paleoceanographic studies. The present work is the study of the diatoms from the Paleogene interval of the 356 Hole (DSDP Leg 39) which was drilled at the southwestern slope of Sao Paulo Ridge (Southeastern margin of Sao Paulo Plateau). The rocks of this site belong to distal portions of Santos Basin, and the rocks of this Paleogene interval to the Marambaia Formation. Despite the numerous and diverse diatoms present, this interval was zoned by their planktonic foraminifers and calcareous nannofossils content but not by their diatoms. This study intent provides a biostratigraphical definition to the diatomite content of this interval and briefly discusses their geologic and paleontologic implications. In taxonomic terms, 92 taxa were found with 29 genera, 68 species, 19 species classified as sp., and 6 ontogenetic variants of Asterolampra spp. In biostratigraphic terms, four diatoms biozonas were identified ranging Mesoeocenic to Neoligocenic ages. Four hiatuses were detected, two external to the interval and two internal. The results achieved here require some discussion about the previously correlations made between planktonic foraminifers, calcareous nannofossils and diatoms biozonas of this interval, as well as about the previously sedimentologic patterns described to this interval.
Keywords: Diatomáceas; Platô de São Paulo; Site 356-DSDP 39; Paleógeno; Diatoms; Sao Paulo Plateau; Paleogene; ACCNPQ::Ciências Exatas e da Terra::Geologia